Amplification or suppression: Social networks and the climate change—migration association in rural Mexico. (November 2015) - Nawrotzki, Raphael J.; Riosmena, Fernando; Hunter, Lori M.; Runfola, Daniel M.
Highlights: We model the impact of climate change on international migration from rural Mexico. We employ a novel set of 15 ETCCDI climate change indices based on daily climate data. We examine the influence of social networks on climate change related migration. Warming temperatures and declining precipitation increase international migration. Access to social networks weakens the climate change migration association. Abstract: Increasing rates of climate migration may be of economic and national concern to sending and destination countries. It has been argued that social networks—the ties connecting an origin and destination—may operate as "migration corridors" with the potential to strongly facilitate climate change-related migration. This study investigates whether social networks at the household and community levels amplify or suppress the impact of climate change on international migration from rural Mexico. A novel set of 15 climate change indices was generated based on daily temperature and precipitation data for 214 weather stations across Mexico. Employing geostatistical interpolation techniques, the climate change values were linked to 68 rural municipalities for which sociodemographic data and detailed migration histories were available from the Mexican Migration Project. Multi-level discrete-time event-history models were used to investigate the effect of climate change on international migration between 1986 and 1999. At the household level, the effect of social networks was approximated by comparing the first to the last move, assuming that through the first move a household establishes internal social capital. At the community level, the impact of social capital was explored through interactions with a measure of the proportion of adults with migration experience. The results show that rather than amplifying, social capital may suppress the sensitivity of migration to climate triggers, suggesting that social networks could facilitate climate change adaptation in place.